Antibiotic activity of extracts and essential oils against Propionibacterium acnes (Research, Society and Development, 2020)
Or use of natural products has added technological increase in the area of ​​dermocosmetics. Especially, it does not treat skin processes and affections, such as acne vulgaris - manifested by the presence of the infectious agent Propionibacterium acnes, a strain with growing mechanisms of resistance to antibiotics. The objective is to analyze, by means of a systematic literature review, the antibiotic effect exercised by essential oils and vegetative extracts against P. acnes. For the data queue, the bases Science Direct, Biblioteca Virtual em Saúde (BVS) and Scientific Electronic Library Online (SciELO) were used together with the descriptors: “Plantas Medicinais” “Extratos Vegetais” “Oleos Esenciais” “Propionibacterium acnes”, in Portuguese and English. Adotou-se as a criteria for inclusion of publications for the last 5 years (2015-2020) and experimental studies. And as of exclusion artigos that do not present any action against the strain, replicas between platforms. Support for the application of two descriptors, temporary cut and set criteria, 13 articles will respond to the most significant aspects of the approach. Two studies included, also explored antibacterial potential, synergistic and anti-inflammatory. In large part two studies, and suggested that some metabolites interact with the microbial cell membrane causing deformations and also inhibit the synthesis of nucleic acids related to genetic material and enzymatic activity. Note that the use of essential oils and vegetative extracts arises, as an alternative capable of exercising antimicrobial, synergistic or anti-inflammatory activities, being able to originate or develop new therapeutic approaches.